OPTIMIZATION OF BAMBOO ROOTS PGPR DOSAGE ON MUNG BEAN GROWTH AND YIELD - Nareswari, Aptika Hana Prastiwi; Saptorini, Saptorini; Noviady, Ikhsan (Universitas Medan Area, 2025)
The application of plant-growth promoting rhizobacteria (PGPR) offers an eco-friendly approach to enhancing crop growth and productivity. This study assesses the effects of PGPR derived from bamboo roots on growth metrics (e.g., stem diameter and branch count) and yield traits (e.g., pod count, fresh and dry pod weights, and harvested bean weight) of mung bean (Vigna radiata L.). Bamboo roots were selected as a unique source of PGPR because it fosters a favourable environment for beneficial microorganisms, enhancing nutrient absorption in plants. Conducted under controlled conditions, this experiment followed a completely randomized design, tested six PGPR dosage: 0 ml/polybag (H0), 10 ml/polybag (H1), 20 ml/polybag (H2), 30 ml/polybag (H3), 40 ml/polybag (H4), and 50 ml/polybag (H5) applied weekly. Results revealed significant growth promotion during the late vegetative phase, with H3 yielding optimal outcomes improved stem diameter, branch number, pod count, and seed dry weight. Higher dosages (H4, H5) negatively impacted growth, potentially due to microbial competition, nutrient imbalance, or stress. This eco-friendly method demonstrates the potential of bamboo-derived PGPR to boost mung bean productivity, supporting food security and profitability. Further studies should investigate its long-term effects and adaptability across diverse crops and farming systems, enhancing its utility for sustainable agriculture.